THE INFLUENCE OF CELEBRITY ENDORSERS, ADVERTISING AND CREATIVE SALES PROMOTION ON PURCHASE INTENTION IN E-COMMERCE - Teuku Zulkarnaen; Yayang Tiara; Mariyudi; Heriyana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The aim of this study is to understand consumer intentions to purchase, with the aim of predicting future consumer behavior in shopping online. The research results show that advertising has a positive and significant effect on purchase intentions in E-commerce in Lhokseumawe City. Advertising also has an important role in shaping consumer perceptions of the quality and reliability of products sold on Shopee. Creative sales promotion and Celebrity endorsement have a significant impact on purchasing intentions for e-commerce. It is also reflected in increased awareness, positive changes in attitudes towards the brand, increased consumer confidence, and ultimately, influence on purchasing decisions.